Computer modelling of hydrogen defects in the clinopyroxenes diopside and jadeite - Gatzemeier, A.; Wright, Kathleen (Springer-Verlag GmbH, 2006)
Atomistic computer simulation techniques have been employed to model mechanisms of hydrogen incorporation in the clinopyroxenes diopside and jadeite. Calculation of solution reaction energies for the pure phases indicates that hydrogen is most easily incorporated via the formation of [VSi(OH)4]x hydrogarnet type defects. When components of the two phases are mixed, then solution energies can become exothermic. The substitution of Al for Si in diopside and of Mg or Ca for Al in jadeite, provides favourable routes for hydrogen incorporation, with exothermic values of solution energy. Thus the amount of water present in these minerals in the Earth’s upper mantle will vary with composition. Simulation of IR frequencies associated with O–H stretching at specific defect clusters has also been carried out. An analysis of hydrogen–oxygen bond lengths gives good agreement, although comparison of experimental and calculated IR frequencies are problematic. This is partly due to the complexity of experimental spectra, but may also be due in part to deficiencies in the ability of the model to accurately describe the O–H stretching frequency.